Heat-shock protein synthesis by human polymorphonuclear cells (The Rockefeller University Press, 1987)
Mature human neutrophils from peripheral blood are known to be capable of limited protein biosynthetic activity. We now show that these cells are inducible for heat-shock protein synthesis when placed in short- term culture. Synthesis of hsp70 and hsp85 as well as the response to various temperatures and the time course of induction were typical for mammalian cell systems. This heat-shock response was blocked by actinomycin D added before heat exposure. This demonstration that hsp genes can be activated by heat exposure of terminally differentiated neutrophils supports the hypothesis that gene activation can serve a physiological role in these cells and opens up the possibility that synthesis of other gene products is similarly inducible.